Promoting Wellness in Underserved Communities: Issues, Design Guidelines, and Programming - Siggers, Brooke. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Committee: Julian Agyeman.; Keyword: Public health.